2019
DOI: 10.1016/j.jfineco.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Attention allocation and return co-movement: Evidence from repeated natural experiments

Abstract: We study how attention allocation affects the composition of market/industry and firm-specific information in stock prices via repeated natural experiments. Using large jackpots of Taiwanese nationwide lotteries as exogenous shocks to investors' attention, we find: (1) individual stock returns co-move more with the market/industry returns on large jackpot days; (2) large jackpots have stronger effects on stock returns' co-movement with the market than with the industry; (3) the effect of large jackpots on retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…One potential explanation for our results could be that investors are not necessarily more risk-averse but instead are distracted by the terror attack and as a result not focused on the stock market (Barber & Odean, 2013;Dellavigna & Pollet, 2009;Hirshleifer, Lim, & Teoh, 2009;Huang, Huang, & Lin, 2019). If investors pay less attention to the stock market, then we would expect them to naturally decrease their trading activity.…”
Section: The Attention Channelmentioning
confidence: 87%
“…One potential explanation for our results could be that investors are not necessarily more risk-averse but instead are distracted by the terror attack and as a result not focused on the stock market (Barber & Odean, 2013;Dellavigna & Pollet, 2009;Hirshleifer, Lim, & Teoh, 2009;Huang, Huang, & Lin, 2019). If investors pay less attention to the stock market, then we would expect them to naturally decrease their trading activity.…”
Section: The Attention Channelmentioning
confidence: 87%
“…This would imply that these investors are more inclined to process market and sector-wide rather than firm-specific information, leading to increasing comovement of stock returns. This hypothesis has been formally developed by Peng and Xiong (2006) and has already found empirical support, for instance in Huang, Huang, and Lin (2019), Schmidt (2013) or Peng, Xiong and Bollerslev (2007).…”
Section: Non-technical Summarymentioning
confidence: 81%
“…Using the large jackpots of Taiwanese nationwide lotteries as exogenous shocks that attract investors' attention away from the stock market to test the theory's implications. Huang et al (2019) found large jackpot days are linked to lower share turnover and Google search volume for firms but with higher Google search volume for lotteries. Their findings also suggested that large jackpots have a significant spill-over effect on return co-movements with the market, and this effect reduces with the window length.…”
Section: Literature Reviewmentioning
confidence: 93%